Pengaruh Leverage, Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Putri, Siska Oktapia; Hendriyani, Rina Maria (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze the effect of Leverage (DER), Profitability (ROA) and Company Size on Firm Value (PBV) both partially and simultaneously on Banking Companies listed on the Indonesia Stock Exchange during the 2018-2023 period. The independent variables used in this research are Leverage (DER), Profitability (ROA) and Firm Size. Meanwhile, the dependent variable used in this research is Firm Value (PBV). Sampling was carried out using a purposive sampling technique and 12 companies were sampled with 60 observational data. The research method used is a quantitative method with a descriptive approach. The data analysis method used was statistical analysis using SPSS software.The results of the study show that there is a significant influence on Leverage (DER) and Firm Size but there is no significant effect on price-to-book value (PBV) Firm Value. partially, there is a considerable influence on Profitability (ROA) and there is a substantial effect on Company Value and price to Book Value (PBV). The results of the study simultaneously have a significant effect on Leverage (DER), Profitability (ROA) and Firm Size on Firm Value (PBV)..